Regional Arrangement to Increase Tourist Visits in Sumber Harapan Village, Sambas. - suhendra suhendra; Sabahan Sabahan; Andri Hidayat; Feby Nopriandy; Budi Setiawan (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2022)
Sumber Harapan Village is a cultural tourism village known for its songket weaving crafts. Another tourism potential that the village has is a large river that stretches between settlers, wooden roads along the river banks, traditional houses, customs and culture. However, the existence of supporting facilities and infrastructure is still lacking and the arrangement of the village area has not been done properly. Through the PPDM program, the team make serious efforts to solve the through various activities that have been agreed together with mitra. The results of the activities that have been carried out through this program are the creation of plant gates, environmental arrangements in front of the weaving gazebo, the arrangement of the road to the weaving gazebo, the creation of a rest place, the procurement of tourism supporting facilities in the form of canoes and fittings, and the installation of the iconic sign of the tourist village. The results of the service have a major impact on the village community of Sumber Harapan. The existence of plant gates and village icon sign becomes a new photo spot that is crowded. The existence of supporting facilities such as canoes and resting places provides convenience for visitors. Many tourist visits have an economic impact on the villagers of Sumber Harapan in the form of increasing income and potentially opening up new business opportunities such as food stalls, souvenirs or as providers of services such as homestays or guesthouse.